Arts and Design Discourse in Idealogy Journal: Foreword - Ab Gani, Muhamad Abdul Aziz; Ramli, Ishak; Taharuddin, Nurul Shima; Rosman, Muhammad Redza; Nazrin, Nizar; Md Nazri, Haslinda (Idealogy Journal; Vol 7 No 2 (2022): Idealogy Journal (September 2022), 2022)
Arts and Design Discourse